Determinants of Sharia Finance Inclusion among Students in Universitas Riau - M Rizwan; Eriyati Eriyati; Rendra Wasnury; Supriani Sidabalok (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research aimed to examine the factors that influence Universitas Riau students' adoption of Sharia finance. The quantitative approach is used in this study, and both primary and secondary sources of numerical data were used. 204 students from 10 faculties at Universitas Riau were given questionnaires to complete to gather primary data. The literature, including journals, websites, and publications from pertinent institutions, provided the secondary data. Multiple Linear Regression using the SEM-PLS (Structural Equation Modeling–Partial Least Squares) methodology was the analysis technique employed. The results demonstrated that digital service access, Sharia finance literacy, and trust in Sharia finance all significantly and favorably impact Sharia finance inclusion. On the other hand, religiosity has a beneficial but insignificant impact. Research's primary contribution is to illustrate the value of educating students about Sharia finance to prepare the next generation to contribute to the advancement of Sharia economics in the future. This study offers a distinctive contribution to the academic discourse on Sharia finance by focusing specifically on the determinants of Sharia financial inclusion among university students in Indonesia, particularly those at Universitas Riau. While many previous studies explore financial inclusion at the national or industry level, this research uniquely targets the young educated generation as future users and contributors to the development of Islamic finance.